2021
DOI: 10.1101/2021.03.29.21251808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing the results of the application of moving and stationary sinusoidal gratings in the functionally assisted treatment of meridional amblyopia

Abstract: Introduction: Background: The first approach to a frequency-selective visual training in amblyopia had been proposed in the sixties by the physiologist Fergus Campbell. During the stimulation, his grating was moving very slowly, i.e., only once a minute around its axis. Therefore, the CAM-stimulator was based exclusively on the proposed influence of spatial frequency selectivity, however there was no significant contribution of the temporal frequency of the stimulus. Accordingly, we are convinced that this was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…There was an improvement in corrected meridional acuity after treatment with the game using the sinusoidal drifting grating pattern, with a more pronounced improvement of visual acuity noted in the meridian with maximum ametropia. No statistically significant improvement was observed after exercises with the stationary grating [18].…”
Section: Study Rationalementioning
confidence: 76%
See 2 more Smart Citations
“…There was an improvement in corrected meridional acuity after treatment with the game using the sinusoidal drifting grating pattern, with a more pronounced improvement of visual acuity noted in the meridian with maximum ametropia. No statistically significant improvement was observed after exercises with the stationary grating [18].…”
Section: Study Rationalementioning
confidence: 76%
“…In recent decades, there have been several reports on the development of device-based treatments for MA which allow the activation of meridional retinocortical pathways by adequate structured stimuli [16][17][18][19][20].…”
Section: Study Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Beyond CAM treatment, FAVAS relies not only on spatial frequency selectivity of the ambient background stimulus, but also on an interaction of its coordinated temporal frequency parameters with the focal sensory-motoric gaming activity (Kämpf et al 2008). 13,16,17 Previously, Kämpf et al showed that FAVAS had a promising effect. Since the early version of FAVAS focused on the therapeutic aspect of visual acuity stimulation and put less focus on the user-friendliness, gamefication and attention binding aspect, this modification could potentially impact patient adherence.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that a stable outcome of treatment of amblyopia (a visual acuity of at least 0.5) was maintained at 3-year follow-up only in 54% of patients [10,14,15]. In recent decades, there have been several reports on the development of device-based treatments for MA which allow the activation of meridional retinocortical pathways by adequate structured stimuli [16][17][18][19][20].…”
mentioning
confidence: 99%